Fabrication of Cu2O nano crystals by {111} plane-oriented growth - Nguyet, Trieu Thi; Son, Pham Anh; Nho, Vu Thi; Canh, Kieu Thanh (Vietnam Journal of Chemistry, 2015)
Cu2O nano crystals were fabricated by reduction of CuCl2 by hydrazine in presence of sodium dodecyl sulfate (SDS) as a capping ligand in alkaline medium. X-Ray Diffraction results indicated the appearance of single phase of Cu2O possessing cubic crystal system with lattice parameter α of 4.263 nm. By using X-ray Photoelectron Spectroscopy, subsequently, analyzing the binding energy of Cu2p electron, the oxidation sate of copper element was proved to be +1. In presence of SDS, the Cu2O crystals preferred to grow towards {111} plane-orientation. The SEM images showed the difference shapes and sizes of Cu2O single crystals. Under certain conditions, the truncated cube or truncated octahedron was obtained. In these structures, {111} crystal planes were exposed around the surface of Cu2O grains. The amount of hydrazine was considered as the most important factor for tuning the morphology of Cu2O particles. The results of this study is hoped to uncover the exploiting ability of the potential advantages from {111} planes on the surface of Cu2O single crystals.